Talking Books, Selling Selves: Rereading The Politics Of Olaudah Equiano’s Interesting Narrative - Pethers, Matthew (American Studies, 2007)
Olaudah Equiano’s Interesting Narrative (1789) has often been seen as being ambiguously implicated in the emergence of liberal modernity, with Equiano’s self-purchase and free-trade proselytizing marking out both the promise and the danger of economic individualism. This essay, while paying close attention to these arguments, also seeks to move beyond this conceptual paradigm by exploring how Equiano’s autobiography connects with the wider political compexities of the Revolutionary era. In particular, I use recent historiographical debates about the values of the Founding Fathers to reframe the Interesting Narrative within an ideological universe where classical republicanism and modern liberalism existed as forces that were both antagonistic and inseparable. When considered in relation to the social theory of figures as diverse as Adam Smith and Benjamin Rush, Equiano’s pioneering slave narrative can be seen as engaging not only with competing models of liberalism but also with the possibilities and problems of civic humanism. Moving rhetorically between print and profit, self-interest and disinterest, virtue and commerce, the Interesting Narrative stands revealed as a deeply conflicted text which uses a patchwork of political ideas to negotiate the minefields of African-American bondage.